Jejaring Kebijakan dalam Menghadapi Tantangan Tata Kelola Pemerintahan Modern di Kota Bandung - Rizky Ilhami (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze policy networks in addressing the challenges of modern governance in Bandung City. The complexity of urban issues and the demand for transparent, participatory, and adaptive governance have encouraged local governments to involve various non-governmental actors in the public policy process. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, documentation, and observation of actors involved in policy networks within the Bandung City Government. Data analysis was conducted using the Miles and Huberman interactive model. The results show that the policy network in Bandung City has been formed through collaboration between the government, the private sector, academics, and the community. However, the effectiveness of this network still faces various challenges, such as weak coordination between actors, government dominance in decision-making, unclear division of roles and accountability, and low levels of trust and long-term commitment. This study concludes that strengthening the policy network through improved coordination, institutional capacity, utilization of digital technology, and community participation is key to realizing collaborative and sustainable modern governance in Bandung City.